Citizen participation in the Gauteng Provincial Legislature: a theoretical and case study. - de Bruyn, Graeme Howard (My University, 2014)
This study investigated the extent and scope of citizen voice in public decision-making in the Gauteng Provincial Legislature (GPL) from two theoretical perspectives. It is structured around three components; an in-depth exposition of the literature on citizen participation, application of two theoretical frameworks applied to the scope of citizen voice in the GPL and an applied case study approach. This study found that the literature ascribes multiple meanings to citizen participation and that there are incongruities in the manner in which the literature conceptualises, describes the mechanisms, and outlines the intentions, and outcomes of citizen participation. Citizen voice in the GPL is deemed to be contextual to and influenced by the interplay of the socio-political environment, multiple interests, values and sub-systems. The case study approach allows for an expanded analysis of the implicit power dynamics in the GPL and the institutional political processes on the nature and extent of citizen voice. In this study citizen voice is regarded as an opportunity for direct, representational and/or institutional expression of citizen interests in public decisions consolidating democracy, citizenship and legitimate government.The GPL’s policy documents point to a stated intent of democratic public participation conceived and pursued as citizen control, empowerment and partnership. However the conclusion is that this participation vacillates between information sharing and consultations, but not decisionmaking control. The study asserts that the theory on citizen voice in public decision-making is under-developed and there is a disconnection between the literature and citizen experiences.
Keywords: Public policy; Citizen participation; South Africa; Gauteng